2020
DOI: 10.1080/2162402x.2020.1824632
|View full text |Cite
|
Sign up to set email alerts
|

Better prognosis of gastric cancer patients with high levels of tumor infiltrating lymphocytes is counteracted by PD-1 expression

Abstract: The prognostic potential of anti-tumor immune responses is becoming increasingly important in adenocarcinoma of the gastroesophageal junction and stomach (AGE/S) especially regarding the use of immune checkpoint inhibitors. This study analyzes for the first time the prognostic impact of tumor-infiltrating lymphocytes (TILs) and checkpoint inhibitors in a large Caucasian cohort in patients with AGE/S. We screened tissue samples from 438 therapy-naïve patients with AGE/S undergoing surgery between 1992 and 2005,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 46 publications
(64 reference statements)
2
12
0
Order By: Relevance
“…We previously reported on longer survival of patients with AEG/ASs exhibiting high CD4 + cell infiltration [ 29 ]. Even though a non-statistical significant trend towards correlation between activin protein expression and overall survival was seen in tumors exhibiting a low CD4 + T-cell infiltration (high 57.4 +/− 11.0 months versus low 47.1 +/− 5.7 months, p = n.s.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported on longer survival of patients with AEG/ASs exhibiting high CD4 + cell infiltration [ 29 ]. Even though a non-statistical significant trend towards correlation between activin protein expression and overall survival was seen in tumors exhibiting a low CD4 + T-cell infiltration (high 57.4 +/− 11.0 months versus low 47.1 +/− 5.7 months, p = n.s.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical analysis of expression of CD3 + , CD4 + and CD8 + , as well as PD-1 and PD-L1 was performed on consecutive TMA sections using a specific monoclonal antibody as previously described. Correlation of prognosis with these factors in this cohort as well as representative images of the stainings were previously published [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…The suppression of anti-tumor T cell responses is further magnified by increased PD-L1 expression on tumor cells, thereby upregulating tumor progression. This also could explain why good prognosis of gastric cancer cases with high TILs levels as reported by some studies is countered by expression of PD-1 expression (24).…”
Section: Discussionmentioning
confidence: 90%
“…However, the effect of PD-L1 on overall survival is still controversial. Some studies reported PD-L1 as a poor prognostic factor (18,24), whereas, others either found it was a good indicator (20) or it had a non-significant relationship with overall survival (17).…”
Section: Discussionmentioning
confidence: 99%
“…ICI treatments benefit some patients with metastatic cancers, but predictive biomarkers are urgently needed. PD-L1 has been shown to be overexpressed in numerous cancer cell types and is associated with different clinical outcomes, either better or worse, depending on the tumor category (12)(13)(14)(15). PD-L1 is one of the immune-checkpoint molecules that regulates Type 1 T helper (Th1) immune responses and mediates cancer immune evasion.…”
Section: Introductionmentioning
confidence: 99%